Technical Performance of Textile-Based Dry Forehead Electrodes Compared With Medical-Grade Overnight Home Sleep Recordings - Matias Rusanen (IEEE, 2021)
The current clinically used electroencephalography (EEG) sensors are not self-applicable. This complicates the recording of the brain’s electrical activity in unattended home polysomnography (PSG). When EEG is not recorded, the sleep architecture cannot be accurately determined, which decreases the accuracy of home-based diagnosis of sleep disorders. The aim of this study was to compare the technical performance of FocusBand, an easily applicable textile electrode headband, to that of clinical EEG and electrooculography (EOG) electrodes. Overnight unattended recordings were conducted at participants’ ( $n =10$ ) homes. Signals were recorded using a portable Nox A1 PSG device. The FocusBand’s forehead EEG (Fp1-Fp2) signals contained features that are visible at both, the standard EEG (F4-M1) and EOG (E1-M2) signals. The FocusBand’s EEG signal amplitudes were significantly lower compared to standard EEG (F4-M1; average difference 98%) and EOG (E1-M2; average difference 29%) signals during all sleep stages. Despite the amplitude difference, forehead EEG signals displayed typical EEG characteristics related to certain sleep stages. However, the frequency content of the FocusBand-based signals was more similar to that of the standard EOG signals than that of standard EEG signals. The majority of the artifacts seen in the FocusBand signals were related to a loosened headband. High differences in the frequency content of the compared signals were also found during wakefulness, suggesting susceptibility of the textile electrodes to electrode movement artifacts. This study demonstrates that the forehead biopotential signals recorded using an easily attachable textile electrode headband could be useful in home-based sleep recordings.